Effects of chlorpyrifos on the freshwater mussel Unio elongatulus eucirrus (Bourguignat, 1860), with a focus on neurotoxicity and oxidative stress responses - Faruk Zorlar; Engin Şeker; Ayşegül Pala (Revista Científica)
This study set out to investigate the effects of the organophosphate insecticide chlorpyrifos (CPF) on certain biochemical parameters of the freshwater mussel Unio elongatulus eucirrus. Mussels were exposed to varying concentrations of CPF (10, 20, and 40 µg·L-1) for duration of 96 hours. Samples were collected from the mussels at the 24th and 96th hours of the experiment. The results indicated that exposure to CPF concentrations led to a decline in the activities of acetylcholinesterase (AChE), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities and, accompanied by an increase in malondialdehyde (MDA), and decreased reduced glutathione (GSH) levels in mussels. In conclusion, the present study demonstrates that CPF caused AChE inhibition, formation of oxidative stress, and negative effects on certain antioxidant parameters in the freshwater mussel U. elongatulus eucirrus.